Stroke volume does not plateau in female endurance athletes - Wang, E.; Solli, G. S.; Nyberg, S. K.; Hoff, J.; Helgerud, J. (International Journal of Sports Medicine, 2012)
It has been a long-lasting debate whether the heart's stroke volume (SV) increases at high aerobic intensities or plateau. Further, sex and level of aerobic power are shown to influence the response. The purpose of this study was to investigate the SV at increasing intensities in elite female athletes and moderately trained females. 13 elite athletes and 11 moderately trained controls with maximal oxygen consumption (VO2max) of 67.1±6.1 and 49.5±2.3 mL /min - 1 /kg - 1, respectively, were recruited. SV was measured at rest, and running on a treadmill at 40%, 60%, 80% and 100% of VO2max using the single breath acetylene uptake (SB) technique. Both groups showed a significant (p<0.05) increase in SV from 40% of VO2max to VO2max, with increases from 105.3±19.0 to 129.1±16.3 mL? beat-1 for the elite females and from 68.7±21.7 to 82.7±14.0 mL /beat - 1 for the moderately trained. No differences were observed between groups in these increases, but the elite athletes displayed a larger (p<0.05) SV at all intensities. It is concluded that the SV increases at high aerobic intensities both in elite athlete females and moderately trained females.